Optimization of Science Techno Park Institut Pertanian Bogor Business Incubation Program Information Through Sainstek Podcast - Azzahra Pramesti Ashari; Wahyu Budi Priatna (Communica : Journal of Communication, 2026)
This study aims to identify strategies for optimizing the dissemination of information on the Science Techno Park (STP) Institut Pertanian Bogor business incubation program through podcasts as an interactive digital communication medium aligned with technological developments. The research employed a descriptive qualitative method with data collected through interviews, observation, and documentation involving the STP IPB Website and Social Media Development Team. The findings indicate that the implementation of Regina Luttrell’s Circular Model of SoMe for Social Communication, particularly in the Share stage, has been applied in managing the “Sainstek Podcast.” The Circular Model of SoMe when a company distributes something; the company can simultaneously manage, interact with, and optimize its message. This study is novel because Sainstek Podcast is an innovation by STP IPB that used to disseminate information about business incubation program. However, the Optimize, Manage, and Engage stages have not been fully implemented, resulting in limited effectiveness in information dissemination. Overall, the podcast holds significant potential to expand audience reach, foster two-way communication, and enhance public understanding of STP IPB’s business incubation programs comprehensively because it flexibility of access, content personalization, broad audience reach, educational potential, and low production costs.